Glutathione sulfotransferase inhibition activity of a self-fermented beverage, Kanji. (1st January 2017) - Latif, Abida; Hussain, Khalid; Shehzadi, Naureen; Islam, Muhammad; Khan, Muhammad Tanveer; Anwar, Rukhsana; Khan, Humaira Majeed; Bukhari, Nadeem Irfan
Abstract: Context: Kanji, a liquid preparation of roots of Daucus carota L. ssp. sativus (Hoffm.) Arcang. var. vavilovii Mazk. (Apiaceae), may inhibit glutathione sulfotransferase (GST) activity due to ferulic acid content. Objectives: GST inhibition activity and characterization of Kanji and methanol extract of D. carota roots, and oral absorption pattern of ferulic acid from Kanji in rats. Materials and methods: GST inhibition activity of Kanji and methanol extract of D. carota roots in concentration range 0.001–100.00 mg/mL was determined using Sprague Dawley rat liver cytosolic fraction. Methanol extract upon column chromatography gave ferulic acid, which was used to characterize Kanji and determine its oral absorption pattern in Wistar rats. Results: The GST inhibition activity of Kanji (100.00 μg/mL), methanol extract of D. carota roots (100.00 μg/mL) and tannic acid (10.00 μg/mL, positive control) was found to be 0.162 ± 0.016, 0.106 ± 0.013 and 0.073 ± 0.004 μM/min/mg, respectively. Different Kanji samples and methanol extract contained ferulic acid (0.222–0.316 mg/g) and 0.77 mg/g, respectively. Ferulic acid did not appear in plasma after oral administration of Kanji. Discussion: Kanji having solid contents 80.0 μg/mL, equivalent to 0.0025 μg/mL ferulic acid, does not inhibit the activity of GST. The oral administration of Kanji, in human equivalent dose (528 mg/kg, 16.67 μg ferulic acid), to rats indicated poor absorption of ferulic acid. Conclusion: Kanji having solid contents 14–36 mg/mL does not inhibit GST activity, hence may not interfere with drugs that are the substrates of GST, if taken concomitantly.